Memory impairment in young women at increased risk of depression: influence of cortisol and 5-HTT genotype - Mannie, Z; Barnes, J; Bristow, G; Harmer, C; Cowen, P (Cambridge University Press, 2009)
Background: Memory deficits are common in depressed patients and may persist after recovery. The aim of the present study was to determine whether memory impairments were present in young women at increased familial risk of depression and whether memory performance was related to either cortisol secretion or to allelic variation in the promoter region of the serotonin transporter gene (5-HTT). Method: Young women (n=35, age range 16-21 years) with no personal history of depression but with a depressed parent (FH+) carried out the Rey Auditory Verbal Learning Test (RAVLT). They also provided samples for the measurement of waking salivary cortisol and for 5-HTT genotyping. An age-matched control group of women (n=31) with no family history of depression were similarly studied. Results: The FH+ participants had decreased immediate recall and recognition memory compared to controls. The impairment in recall, but not recognition, correlated negatively with increased cortisol secretion in FH+ subjects. There was no significant effect of 5-HTT allelic status on either memory or waking cortisol secretion. Conclusions: Impairments in declarative memory are present in young women at increased genetic risk of depression and may be partly related to increased cortisol secretion. Further studies are needed to explore the neural mechanisms underlying the memory impairments and whether they predict the development of clinical illness.